Analysis of High School Students’ Argumentation Ability in the topic of Buffer Solution - Ninda Dwi Cahya Devi; Elfi Susanti VH; Nurma Yunita Indriyanti (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2018)
Argumentation is scientific discourse in science learning that is used as a link between knowledge from an environment and concepts in science learning. Through argumentation skills can be controlled student understanding in connecting facts with concepts in learning. This study aims to analyze students' argumentation ability on buffer solution subject. Students' argumentation ability is divided into 4 levels; level 1 (claims), level 2 (claims with data), level 3 (claims with data and one rebuttal), and level 4 (claims with more than one rebuttal). Data analysis was done by a qualitative descriptive method using a case study method. The case study method was chosen so that a study of 92 students who were research participants could be carried out in depth and comprehensive. The results obtained that the students' argumentation ability was at level 1 and level 2 argumentation. This shows that students' argumentation skills are still at low and medium levels. The results of this study can be used as a basis for improving the quality of teaching and further research.